2020
DOI: 10.1039/d0fo00066c
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bioactive compounds in defatted hempseed (Cannabis sativaL.) by UHPLC-HRMS/MS and anti-inflammatory activity in primary human monocytes

Abstract: Anti-inflammatory effects on human monocytes by phenolic amides present in defatted hempseed fractions (Cannabis sativa L.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…Hemp inflorescences biosynthesise quite unique health beneficial phytocannabinoids, while hemp seeds are an excellent source of high-value oil, proteins, and valuable micronutrients [6], including health beneficial bioactive compounds [7,8]. For instance, Pihlanto et al [9] reported 5.88-10.63 mg total phenolic content (expressed in mg of gallic acid equivalents) per gram of dry defatted hemp seed flour, which was also confirmed by Rea et al [10].…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Hemp inflorescences biosynthesise quite unique health beneficial phytocannabinoids, while hemp seeds are an excellent source of high-value oil, proteins, and valuable micronutrients [6], including health beneficial bioactive compounds [7,8]. For instance, Pihlanto et al [9] reported 5.88-10.63 mg total phenolic content (expressed in mg of gallic acid equivalents) per gram of dry defatted hemp seed flour, which was also confirmed by Rea et al [10].…”
Section: Introductionmentioning
confidence: 72%
“…Sweet grass extracts were reported as being very strong antioxidants in rapeseed oil [30], and later 5,8-dihydroxycoumarin and its glycoside were identified as the main radical scavengers and new natural compounds [12]. Recently, Martinez et al [8] reported that the fractions isolated with a hydroethanolic mixture and ethyl acetate from the defatted press-cake with hexane hempseeds contained N-transcaffeoyltyramine as one of the main bioactives and reduced the inflammatory competence of lipopolysaccharide-treated human primary monocytes.…”
Section: Characterisation Of Ingredientsmentioning
confidence: 99%
“…Studies have shown that caffeoyltyramine is the major compound in the fraction with a concentration above 6.36 mg/g extract. 17 …”
Section: Resultsmentioning
confidence: 99%
“…These compounds derive from the products of conjugation between phenolic acids and arylmonoamines, such as tyramine and octopamine, which are present in hempseed in large proportions 19 , 20 and in high quantities. 17 Hempseed can be a source of potential candidates with application in neurodegenerative diseases. It has also been reported that N -methylated tyramine derivatives of Ginkgo biloba can cross the BBB.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of phytoconstituents, multiple studies describing diverse analytical methods for the determination of cannabinoids and terpenes in cannabis matrices have been recently reported [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Furthermore, SMPRs for the quantitation of cannabinoids in cannabis concentrates have been published [ 38 ], and several literature reviews outlining the most up‐to‐date information in terpene and potency analysis are also available [ 7 , 8 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%